TIME IN PROFESSORS’ LIVES THROUGH THE EYES OF SOCIOLOGISTS - Polina A. Ambarova; Garold E. Zborovsky (Высшее образование в России)
The authors analyze the results of a qualitative study of the temporal behaviour strategies of representatives of the research pedagogical and scientific community, investigate the temporal behaviour strategies in the context of cognitive, emotional and behavioral aspects by using the method of depth semiformalized interview. The temporal behavior strategies of university professors are considered as a specific method of forming and realization of their human capital.